Integrated bioinformatics and in silico approaches reveal the biological targets and molecular mechanisms of 1,25-dihydroxyvitamin D against COVID-19 and diabetes mellitus - Zeng, Fanqiang; Xu, Yongli; Tang, Chaoling; Yan, Zhigang; Wei, Chaohe (Frontiers in Nutrition, 2022)
Coronavirus disease 2019 (COVID-19) and diabetes mellitus (DM) are two major diseases threatening human health. The susceptibility of DM patients to COVID-19 and their worse outcomes have forced us to explore efficient routes to combat COVID-19/DM. As the most active form of Vitamin D, 1,25-dihydroxyvitamin D [(1,25(OH)2D)] has been shown a beneficial effect in the treatment of COVID-19/DM. However, the anti-COVID-19/DM mechanisms of 1,25(OH)2D remain unclear. In this study, an approach combining network pharmacology and molecular docking was performed to reveal the potential hub target genes and underlying mechanisms of 1,25(OH)2D in the treatment of COVID-19/DM. The hub targets and interaction pathways related to 1,25(OH)2D were identified by integrating the key 1,25(OH)2D-target-signaling pathway-COVID-19/DM networks. Fifteen hub targets of 1,25(OH)2D against COVID-19DM were determined, including EGFR, PIK3R1, PIK3CA, STAT3, MAPK1, ESR1, HSP90AA1, LCK, MTOR, IGF1, AR, NFKB1, PIK3CB, PTPN1 and MAPK14. An enrichment analysis of the hub targets further revealed that the effect of 1,25(OH)2D against COVID-19/DM involved multiple biological processes, cellular components, molecular functions and biological signaling pathways. Molecular docking disclosed that 1,25(OH)2D docked nicely with the hub target proteins, including EGFR, PIK3R1 and PIK3CA. These findings suggested that the potential mechanisms of 1,25(OH)2D against COVID-19/DM may be related to multiple biological targets and biological signaling pathways.